Study on Gravity Compensation of RCM Mechanism of Slave Manipulator - Baoping Ma; Fan Zhang; Zhaoying Zhang; Xun Zou; Guosheng Zhang (Jixie chuandong)
In order to improve the positioning accuracy and motion stability of endoscopy surgery robot with remote motion center (RCM) of slave manipulator，the equivalent centroid position of the component is obtained by dynamic equivalence of slave manipulator，and the gravity compensation of the manipulator is carried out by the pull spring-rope wheel. Then the dynamic model of RCM mechanism from the slave manipulator is established according to the Lagrange equation，and the gravity compensation is carried out by the method of calculating moment. By comparing and analyzing the motion response curves of each joint of the manipulator after gravity compensation with Adams，it shows that gravity compensation model can effectively compensate gravity items.